HUBUNGAN ANTARA KELINCAHAN DAN FLEKSIBILITAS TERHADAP HASIL DRIBBLE EKSTRAKURIKULER BOLA BASKET SMA N 1 KEDUNGWUNI - Ilmiyah Ilmiyah; Moch Senoadji Karjadi (Unnes Journal of Sport Sciences, 2023)
Dribble is dribbling to get past the opponent, so agility and flexibility play a role in dribbling. The purpose of the study where to determine: 1) the relationship between agility and dribble female players, 2) the relationship between flexibility and dribble female players, 3) the relationship between agility and flexibility with dribble female players, 4) the relationship between agility and dribble for male players, 5) the relationship between flexibility and dribbling for male players, 6) the relationship between agility and flexibility for male players. The research method is correlational. The sample are 34 players. The whole is used as a sample. Data collection used tests and measurements. The data analysis technique used multiple regression. The results showed that Fcount: 1) agility to dribble results obtained 6.528 significance value 0.022 <0.05 for female players, and 6.158 significance value 0.025 <0.05 for male players, 2) flexibility to dribble results obtained 5,428 significance value 0.034 <0 0.05 for female players, and 0.664 a significance value of 0.428 > 0.05 for male players, 3) agility and flexibility on dribble results obtained 3.765 a significance value of 0.049<0.05 for female players, and 4.168 a significance value of 0.038 for male players. The conclusions of this research is: 1) there is a relationship between agility and dribble results, 2) there is a relationship between flexibility and dribble results for female players, and there is no relationship between male players, 3) there is a relationship between agility and flexibility on the results of dribbling.